Strategic Approaches to Increasing the Investment Attractiveness through a Supply Chain Management: Foreign and Domestic Experience - Sorokina, Ekaterina (International Journal of Supply Chain Management, 2020)
The study proposes the definitions of the concepts of "supply chain management", "investment attractiveness of supply chain managements", "increasing the investment attractiveness of a supply chain management" and "investment gap". The methodological foundations for assessing the investment attractiveness of regions are presented. The study summarizes strategic approaches to increasing the investment attractiveness of the region proposed by Russian and foreign scientists and researchers. The research describes strategic approaches to increasing the investment attractiveness of a supply chain management with due regard to the systemic factors of increasing the investment attractiveness of a supply chain management: the development and implementation of strategic planning, targeted training of personnel. The key elements of a strategy to increase the investment attractiveness of a supply chain management, in particular, strategic indicators and measures, have been proposed. The implementation of the strategic approaches described in the study will increase the number of regional projects and the efficiency of investment resource management, improve the socio-economic development of the area, as well as the coverage of measures aimed at investment development.